ผลของขนาดใบกวนต่อการแขวนลอยของอนุภาค - วรินทร์ บุญแม้น (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The effect of propeller size on particulate suspension was investigated using a baffled mixing tank of 0.3 m diameter and 0.5 m height. Three propeller sizes corresponding to the ratios between propeller diameter and tank diameter of 0.33, 0.50, and 0.67 were used. It was found that an increase of propeller diameter enhanced the uniformity of suspension, but not the fraction of solid suspension due to an occurrence of dead zone at the bottom of the tank. In addition, the investigations were further conducted by varying the vertical position of propeller (corresponding to the ratios of propeller height to tank diameter of 0.17, 0.25, and 0.33), agitation speed (100, 150, 200, and 250 rpm), solid concentration (2.5%, 5%, and 7.5% w/v), and particle size (75-150 µm and 180-300 µm). The results indicated the importance of energy dissipated due to secondary flow, rate of energy supplied by propeller, potential for sediments in gaining momentum from fluid and being suspended, and relativity between drag force and gravity.